Non‐operative adjuncts for the prevention of mastectomy skin flap necrosis: a systematic review and meta‐analysis. Issue 1 (14th November 2022) - Tang, Nicholas; Li, Henry; Chow, Yvonne; Blake, William
Abstract: Background: Native skin flap necrosis is a potentially devastating complication following skin‐sparing or nipple‐sparing mastectomy with a reported incidence of as high as 30%. Treatment depends on the depth and extent of tissue necrosis and can range from dressings to surgical debridement and further reconstruction. This can have implications on patient physical and psychological wellbeing as well as cost of treatment. This study aims to identify and appraise cost‐effective non‐surgical adjuncts for the prevention of native skin flap necrosis. Methods: A systematic review was performed using the preferred reporting items for systematic reviews and meta‐analyses (PRISMA) statement and structured around existing recommended guidelines. A search of MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature and ClinicalTrials.gov was performed with the medical subject headings 'mastectomy' and 'flap necrosis'. After exclusion, 12 articles were selected for review and analysed. Results: A total of 8439 mastectomies were performed on 7895 patients. Preventative non‐surgical adjuncts that demonstrated statistically significant reduction in mastectomy flap necrosis included topical nitroglycerin ointment ( P = 0.000), closed‐Incision negative pressure wound therapy ( P = 0.000), topical dimethylsulfoxide ointment ( P = 0.03), oral cilostazol ( P = 0.032), and local heat pre‐conditioning ( P = 0.047). Conclusions: This study identifies multiple adjuncts that may aid in preventing mastectomy skin flap necrosis, especially in high‐risk patients. Further studies could aim to define standardized protocols and compare the various adjuncts in different circumstances. Abstract : A systematic review assessing non‐operative adjuncts for the treatment of post‐operative mastectomy flap necrosis.